Evaluation of the effectiveness of a Virtual Reality-based exercise program for Unilateral Peripheral Vestibular Deficit - Rosiak, Oskar; Krajewski, Krzysztof; Woszczak, Marek; Jozefowicz-Korczynska, Magdalena (Journal of vestibular research, 2019)
BACKGROUND: Recently, two types of movement sensors have been introduced into Virtual Reality (VR) therapy: motion trackers and force-plate platforms. Combining these two methods could produce better rehabilitation outcomes. Such devices, encompassing motion trackers and force platforms, are referred to as “hybrid” VR units. OBJECTIVE: To assess the effectiveness of a low-cost hybrid VR based vestibular rehabilitation program METHODS: A prospective, non-randomized, controlled group study comparing training using a hybrid VR unit (Group 1 n = 25) vs. static posturography with visual feedback (Group 2 n = 25) in patients with peripheral vestibular dysfunction was conducted. The subjects underwent 10 training sessions over 10 days (30 minute sessions). All were examined on a posturography platform at the start and 1 month after rehabilitation and completed the Vertigo Symptom Scale – Short Form (VSS-SF) questionnaire. RESULTS: Both groups demonstrated improvement in posturographic parameters, which were statistically significant, but when comparing results between both groups there were no differences. The patients reported improvement in their subjective perception of symptoms on the VSS-SF scale, which were statistically significant in both groups, but greater in the VR group. CONCLUSIONS: Both methods reduce postural sway, however subjective reduction of symptoms was greater in the VR group.